The Sharia Hotels In Surakarta And Yogyakarta For World Citizens: A Linguistic Analysis - Putri Juli Pamungkas; Vilya Lakstian Catra Mulia (Jurnal Dialog, 2020)
Linguistic qualitative research using appraisal theory is descriptively undertaken on the English websites of the sharia hotels in Surakarta and Yogyakarta. The data are analyzed on the basis of Appraisal Theory coined by Martin & White (2005) relating to kinds of attitude reflected by language that are negotiated in the texts, level of engaged feelings, and social values. This research investigates the kinds of attitude reflected by language on the data sources available on the websites of the sharia hotels in Surakarta and Yogyakarta. Using document analysis technique, the research data are analyzed in the level of words in the clauses and sentences. The research found various language attitude implemented in the sharia hotels in Surakarta and Yogyakarta in attracting customers’ attention. This research does not only limit itself in finding the dominant factors, but also analyzing meanings of using those attitudes. Penelitian kualitatif bahasa dengan teori appraisal ini dilakukan pada berbagai situs hotel syariah berbahasa Inggris di Surakarta dan Yogyakarta secara deskriptif. Data dianalisis dengan Teori Appraisal yang dikemukakan oleh Martin & White (2005) terkait beragam jenis sikap yang direfleksikan dengan bahasa yang dinegosiasikan dalam teks, kekuatan perasaan yang terlibat, dan nilai sosial. Penelitian ini bertujuan menemukan jenis sikap yang direfleksikan pada bahasa pada sumber data yaitu berbagai situs hotel syariah di Surakarta dan Yogyakarta. Dengan teknik analisis dokumen, data penelitian dianalisis pada tingkat kata pada klausa dan kalimat. Hasil dari penelitian ini adalah menemukan beragam sikap berbahasa yang dibangun oleh hotel-hotel syariah di Surakarta dan Yogyakarta dalam menarik perhatian konsumen. Penelitian ini tidak hanya terbatas pada memperoleh mana yang dominan, tetapi juga menganalisis makna dari penggunaan sikap itu.